German version of the intuitive eating scale: Psychometric evaluation and application to an eating disordered population. (1st October 2016) - van Dyck, Zoé; Herbert, Beate M.; Happ, Christian; Kleveman, Gillian V.; Vögele, Claus
Abstract: Intuitive eating has been described to represent an adaptive eating behaviour that is characterised by eating in response to physiological hunger and satiety cues, rather than situational and emotional stimuli. The Intuitive Eating Scale-2 (IES-2) has been developed to measure such attitudes and behaviours on four subscales: unconditional permission to eat (UPE), eating for physical rather than emotional reasons (EPR), reliance on internal hunger and satiety cues (RHSC), and body-food choice congruence (B-FCC). The present study aimed at validating the psychometric properties of the German translation of the IES-2 in a large German-speaking sample. A second objective was to assess levels of intuitive eating in participants with an eating disorder diagnosis (anorexia nervosa, bulimia nervosa, or binge eating disorder). The proposed factor structure of the IES-2 could be confirmed for the German translation of the questionnaire. The total score and most subscale scores were negatively related to eating disorder symptomatology, problems in appetite and emotional awareness, body dissatisfaction, and self-objectification. Women with eating disorders had significantly lower values on all IES-2 subscale scores and the total score than women without an eating disorder diagnosis. Women with a binge eating disorder (BED) diagnosis had higher scores on the UPE subscale compared to participants with anorexia nervosa (AN) or bulimia nervosa (BN), and those diagnosed with AN had higher scores on the EPR subscale than individuals with BN or BED. We conclude that the German IES-2 constitutes a useful self-report instrument for the assessment of intuitive eating in German-speaking samples. Further studies are warranted to evaluate psychometric properties of the IES-2 in different samples, and to investigate its application in a clinical setting.